The constraints and prospects facing the development of growth of the small businesses in the Giyani area - a case study of the Giyani Business Centre - Maswanganyi, Willie Masiza (University of Limpopo, 2005)
Refer to Document
Thesis (M.Dev.) -- University of Limpopo, 2005
Keywords: Small business development; Giyani Business Centre; Business intitiatives - South Africa; Black business enterprises - South Africa